Signaling metabolite β-aminoisobutyric acid as a metabolic regulator, biomarker, and potential exercise pill - Yi, Xuejie; Yang, Yang; Li, Tao; Li, Menghuan; Yao, Tingting; Hu, Guangxuan; Wan, Genmeng; Chang, Bo (Frontiers in Endocrinology, 2023)
Signaling metabolites can effectively regulate the biological functions of many tissues and organs. β-Aminoisobutyric acid (BAIBA), a product of valine and thymine catabolism in skeletal muscle, has been reported to participate in the regulation of lipid, glucose, and bone metabolism, as well as in inflammation and oxidative stress. BAIBA is produced during exercise and is involved in the exercise response. No side effect has been observed in human and rat studies, suggesting that BAIBA can be developed as a pill that confers the benefits of exercise to subjects who, for some reason, are unable to do so. Further, BAIBA has been confirmed to participate in the diagnosis and prevention of diseases as an important biological marker of disease. The current review aimed to discuss the roles of BAIBA in multiple physiological processes and the possible pathways of its action, and assess the progress toward the development of BAIBA as an exercise mimic and biomarker with relevance to multiple disease states, in order to provide new ideas and strategies for basic research and disease prevention in related fields.